Strategy for Handling Student Academic Fraud in Maintaining Learning Condusiveness at Islamic Boarding Schools (Case Study at TMI Al-Amien Prenduan) - Fajar Tsulits Tamam; Ach. Nurholis Majid (al-Afkar, Journal For Islamic Studies, 2025)
The strategy of handling Academic Fraud is carried out to maintain the conduciveness of student learning in pesantren, in this case the fraud found is student delinquency in the form of santri violations of the rules set at the pesantren, especially TMI Putra Al-Amien Prenduan, such as not attending class, not using official languages (Arabic-English) and so on. The objectives in this study are to describe the strategies in handling student Academic Fraud; to describe the implications of handling Academic Fraud on student learning conduciveness and to describe the obstacles found in handling student Academic Fraud. This type of research is field research with a qualitative approach method, whose data sources are obtained directly in the field by collecting data through observation, interviews and documentation with several sources who have responsibilities in handling student Academic Fraud in pesantren. The conclusion of this study is that there are three strategies in handling student Academic Fraud, namely preventive strategies, curative strategies and reprensive strategies. The implications found in maintaining the conduciveness of student learning are divided into two, namely implications within the school environment and implications outside the school environment. Also, the obstacles found in handling student Academic Fraud are from internal and external factors.